Mortality at the county level in the USA-Mexico and USA-Canada border regions - Melanie Joerger; Onofre Alves Simões (Estudios Fronterizos, 2024)
The areas near a country border have interesting demographics since they are the zones where two cultures collide. The USA has two long land borders with Canada and Mexico. Mortality between 1999-2019 is examined at the county level in the two border regions, compared to the non-border regions of the border states. Analysis is based on single figure indices, with combinations of confounders age, gender and cause of death. Findings confirm differences between border and non-border regions, with opposite results at each border. As far as is known there is no previous mortality study concerning both borders and therefore the contribution of the work is to demonstrate the differences between the border and non-border regions for the two borders and discuss possible reasons. Further, we show that the more detailed analysis at the county level, even with certain data limitations, gives important insights to the topic.